2012
DOI: 10.14704/nq.2012.10.4.608
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Brain Dynamics of Understanding Social Versus Private Intentions: An Electrical Neuroimaging Study

Abstract: Although a growing body of research provides critical information about the spatio-temporal dynamic of the brain network mediating the understanding of causality between an action and its outcome at the individual level, little remains known about this cognitive process when the action outcome has a social connotation. To address this question, we recorded electrical brain activity from 16 healthy adults while they performed an intention understanding task including actions with three different types of causal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Consistent with Wang et al’s (2012) ERP study on intention processing, the present results found that the neural activity associated with intention reasoning had a long duration in centro-parietal regions. The divergence of waveforms started from around 700 ms and lasted later than 1,100 ms, which was longer than the time duration reported by previous ERP studies about desire and belief (Bowman et al, 2012; Geangu et al, 2013; Jiang, Li, et al, 2016; Jiang, Wang, et al, 2016; Liu et al, 2004; Liu, Meltzoff, & Wellman, 2009; Liu, Sabbagh et al, 2009; Meinhardt et al, 2011; Sabbagh & Taylor, 2000; Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with Wang et al’s (2012) ERP study on intention processing, the present results found that the neural activity associated with intention reasoning had a long duration in centro-parietal regions. The divergence of waveforms started from around 700 ms and lasted later than 1,100 ms, which was longer than the time duration reported by previous ERP studies about desire and belief (Bowman et al, 2012; Geangu et al, 2013; Jiang, Li, et al, 2016; Jiang, Wang, et al, 2016; Liu et al, 2004; Liu, Meltzoff, & Wellman, 2009; Liu, Sabbagh et al, 2009; Meinhardt et al, 2011; Sabbagh & Taylor, 2000; Zhang et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Results indicated that differential electrical activities were elicited by private intentions compared with communicative intentions during the period between 400 and 600 ms post-stimulus. The mean amplitudes of the late positive component (LPC) for communicative intentions were significantly larger than those for private intentions (Wang et al, 2012). Furthermore, social intentions, both kind and hostile, elicited more positive LPC amplitudes than those for the non-interactive condition in the 700–800 ms post-stimulus period (Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations